‘Open Access’ or ‘Open Excess’?: libraries at a crossroads - Leo Waaijers (Insights: The UKSG Journal, 2015)
Comparing the costs of open access (OA) and subscriptions is a hot topic at the present time. However, the results of such comparisons often raise questions. This article attempts to provide a more systematic analysis in the form of a question and answer approach. The author states that, in the absence of a market for academic publishing, the concept of average publication fees cannot be used for this purpose. A number of attempts are being made to create such a market, but new contracts for hybrid journals may thwart these initiatives. Libraries are at a crossroads. Will they continue in their current role of money collectors for publishers or revert to their original profession: independent quality control? For the time being, the strict OA policy followed by the Wellcome Trust in the UK has generated a better option for cost comparison.